Analisis Laju Pertumbuhan dan Kontribusi Sektor-Sektor Pembentuk Produk Domestik Regional Bruto (PDRB) pada Kabupaten Daerah Tertinggal di Provinsi Nusa Tenggara Timur Tahun 2017-2019 - Slamet Widodo (Pusat Kajian Anggaran, 2021)
The development of underdeveloped areas is the government's priority development agenda contained in National Long-Term Development Planning (RPJMN). In the 2015-2019 RPJMN, the government has eradicated 60 underdeveloped districts and in the 2020-2024 RPJMN the target of 35 underdeveloped regions can be achieved by 2024. In the 2020-2024 RPJMN period, the government sets 62 underdeveloped districts as stated in Presidential Regulation No. 63 of 2020 concerning the Determination of Disadvantaged Regions for 2020-2024. This study discusses the growth rate and contribution of sectors forming Gross Regional Domestic Product (GRDP) in underdeveloped districts in East Nusa Tenggara Province for the period 2017-2019. The data used is GRDP data for the period 2016-2019. The data processing uses Klassen typology, Location Quotient (LQ), Growth Ratio Model, and Overlay Analysis to determine sectors that receive development priorities. The results showed that the agriculture, forestry, and fishery sectors; real estate sector; government administration sector, defense, compulsory social security; and the construction sector is the leading sector. Meanwhile, the construction sector, electricity and gas supply, water supply, waste management, waste and recycling, mining and quarrying, and corporate services are potential sectors in several districts.